Phase Ib trial of inhaled iloprost for the prevention of lung cancer with predictive and response biomarker assessment - Miller, York E.; Ghosh, Moumita; Merrick, Daniel T.; Kubala, Brandi; Szabo, Eva; Bengtson, Lisa; Kocherginsky, Masha; Helenowski, Irene B.; Benante, Kelly; Schering, Tia; Kim, Jihye; Kim, Hyunmin; et al. (Frontiers in Oncology, 2023)
Iloprost, a prostacyclin analog, has lung cancer preventive activity in preclinical models and improved dysplasia in former smokers in a phase IIb trial. Oral iloprost is currently unavailable.We performed a phase Ib trial of inhaled iloprost in former smokers to assess tolerance and compliance. Participants self-administered nebulized iloprost (5ug) or placebo four (QID) or two (BID) times daily. As QID dose was well tolerated and due to expiration of the placebo, the BID dosing and placebo were eliminated early on in the trial. Bronchoscopy with biopsy at six standard sites was performed at treatment initiation and two months post-iloprost, with exploratory histological analysis. Bulk RNA sequencing, single cell RNA sequencing and an in vitro assay of epithelial progenitor cell iloprost response were performed on a subset of biopsies in an exploratory investigation of response mechanisms and predictive biomarkers. Thirty-four of a planned 48 participants were recruited to the trial. Inhaled iloprost was well tolerated with no adverse events > grade 2. Compliance was 67% in the QID group. The trial was not powered to detect histologic response and none was found. Bulk RNA sequencing of biopsies pre/post iloprost suggest that iloprost is immunomodulatory and downregulates cell proliferation pathways.Single cell RNA sequencing showed an increase in CD8-positive T cells with upregulation of genes in interferon γ signaling. In vitro iloprost response by epithelial progenitor cells correlated with histologic response with kappa coefficient of 0.81 (95% CI 0.47, 1.0). Inhaled iloprost was well tolerated with suboptimal compliance. Molecular analysis suggested that iloprost has immunomodulatory and antiproliferative effects. The progenitor cell iloprost response assay may be a promising avenue to develop predictive biomarkers.